2008
DOI: 10.1002/bin.267
|View full text |Cite
|
Sign up to set email alerts
|

Increasing physical activity through self-monitoring, goal setting, and feedback

Abstract: Excess body weight, especially obesity, is a problem of increasing social significance, and weight gain is often correlated with age. Because physical activity can both decrease current body weight and prevent weight gain, it is an especially suitable target for behavioral intervention. A package intervention consisting of self-monitoring, goal setting, and feedback was used to increase the physical activity of healthy adults. A combined multiple-baseline and reversal design was arranged to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 19 publications
6
73
0
Order By: Relevance
“…The studies by VanWormer (2004) and Normand (2008) demonstrated that a self-management treatment package could increase the number of steps taken by participants, even without programmed reinforcement contingencies. Direct comparisons between these studies and the current one, however, are difficult due to methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by VanWormer (2004) and Normand (2008) demonstrated that a self-management treatment package could increase the number of steps taken by participants, even without programmed reinforcement contingencies. Direct comparisons between these studies and the current one, however, are difficult due to methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback and rewards are other behavior change techniques closely tied to goal setting that can be effective for increasing activity (28, 34, 4244). Feedback can be as basic as providing access to step counts, or more tailored messages designed to motivate activity.…”
Section: Strategies For Promoting Behavior Changementioning
confidence: 99%
“…These activities are reinforced through follow-up automated prompts with persuasive statements sent via iPad mini email accounts [72-74]. Self-monitoring and prompts have significantly improved healthy eating and are associated with increased exercise [75,76]. …”
Section: Methodsmentioning
confidence: 99%